NILAI TASAWUF PESANTREN DAN TRADISI SYAWIR SEBAGAI STRATEGI CULTURAL PROTECTION DARI LONE-WOLF TERRORISM - Chanif Ainun Naim; Adha Hujatulatif (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2021)
AbstractThis article aims to present a fundamental element of pesantren culture which is considered capable of being a cultural strategy in responding to the shift in the modus operandi of terrorism which has reached the stage of lone-wolf terrorism. Pesantren education with the ethical values of Sufism that is owned places the kyai as a central figure who teaches the journey of life and is filled with metaphysical, cosmological, and psycho-religious doctrines which are expected to bring humans to perfection and life peace in total servitude to God through cleansing the heart of despicable qualities, adorn oneself with praiseworthy qualities and spread affection. The tarekat al-Ta'lim wa al-Ta'allum adopted makes pesantren focus on efforts to love science by learning and teaching as the highest position in life. Besides, the bahtsul masail method that is implemented in pesantren trains students to be able to accept differences of opinion as something natural. The three of them form a package of elements of the pesantren that are deeply rooted so that the pesantren and students indirectly have a strategy of resistance against extreme religious understanding.